2013
DOI: 10.4111/kju.2013.54.9.624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Steroid (0.05% Clobetasol Propionate) Treatment in Children With Severe Phimosis

Abstract: PurposeWe report our experience with the use of a topical steroid, 0.05% clobetasol propionate, for the treatment of phimosis with clinical complications.Materials and MethodsThis was a retrospective analysis of the clinical outcomes of all patients presenting with phimosis to a single institution during the time period from October 2008 to May 2012. A total of 88 patients who had a Kikiros retractability grade of 4 or 5 and phimosis-associated clinical complications, such as ballooning of the prepuce, balanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…As to the time required to reach grade 0, on average 47% of patients in both groups required 1 month. A study by Lee and Lee found that 68.2% of the boys achieved success in the same time period [7].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As to the time required to reach grade 0, on average 47% of patients in both groups required 1 month. A study by Lee and Lee found that 68.2% of the boys achieved success in the same time period [7].…”
Section: Discussionmentioning
confidence: 98%
“…Clinical treatment, based on the use of topical corticosteroids for phimosis, poses no risk to patients and there is no signi icant side-effect or systemic effect. However, it is extremely important to perform the preputial massage, since there is no ef icacy in the treatment without it [4,7]. After the period of drug therapy, the need to continue the massage and maintain good local hygiene is stressed, in order to avoid relapses [5].…”
Section: Introductionmentioning
confidence: 99%
“…Clobetasol propionate cream (0.05%) may be used in children for local treatment of stoma granulomas and phimosis . Application to a small nonvascularised area is considered safe .…”
Section: Introductionmentioning
confidence: 99%
“…17 Their use in physiological phimosis was first described by Kikiros et al 18 Subsequent studies showed the response rate for resolution of phimosis to be 68.2% to 95%. 16,[19][20][21][22] Moreno et al 23 subsequently performed a meta-analysis and reviewed 12 randomised controlled trials on the use of different topical steroid formulations, and again confirmed the significant benefit of corticosteroids in the complete or partial clinical resolution of phimosis (risk ratio=2.45; 95% confidence interval, 1.84-3.26).…”
Section: Topical Steroidsmentioning
confidence: 99%